Pelayanan Publik dan Pemenuhan Hak Difabe: Studi tentang Layanan Pendidikan Inklusif Melalui Kasus Pemindahan Difabel dari Sekolah Reguler ke Sekolah Luar Biasa di Yogyakarta - Ika Arinia Indriyany (INKLUSI Journal of Disability Studies, 2015)
Indonesia’s constitution and legislation state that all Indonesiancitizens, including those with a disability, havea right to quality education. To meet this right, the government must ensure that every aspect of schooling and learning are accessible tostudentswith disabilities; however, this is not currentlythe case. Indeed, while inclusive education policy has been in place for years, its implementation is yet to be seen. For example, some children with disabilities are denied admission, while others continue to experience barriers to learning as schools are unable to meet their needs. The perception that disabled students belong only in special, segregated schools is still strongly held by the community, educational practitioners, and policy makers. As such, students with disabilities who register in inclusive schools are expected to meet certain qualifications. Should they fail to meet these requirements students are“returned” to special schools. Thispaper argues that such phenomenon demonstrates the government’s failure to meet its own mandateto ensure and protect the educational rights of persons with disabilities.